Reading Development and Difficulties in Monolingual and Bilingual Chinese Children - Chen, Xi.; Wang, Qiuying; Luo, Yang Cathy; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume explores Chinese reading development, focusing on children in Chinese societies and bilingual Chinese-speaking children in Western societies. The book is structured around four themes: psycholinguistic study of reading, reading disability, bilingual and biliteracy development, and Chinese children$1 (Bs literature. It discusses issues that are pertinent to improving language and literacy development, and complex cognitive, linguistic, and socio-cultural factors that underlie language and literacy development. In addition, the book identifies instructional practices that can enhance literacy development and academic achievement. This volume offers an integrative framework of Chinese reading, and deepens our understanding of the intricate processes that underlie Chinese children$1 (Bs literacy development. It promotes research in reading Chinese and celebrates the distinguished and longstanding career of Richard C. Anderson.s
Foreword -- Preface -- Psycholinguistic Study of Reading Chinese. Morphological Awareness and Learning to Read Chinese and English -- Visual, Phonological and Orthographic Strategies in Learning to Read Chinese -- How Character Reading Can Be Different from Word Reading in Chinese and Why It Matters for Chinese Reading Development -- Fostering Reading Comprehension and Writing Composition in Chinese Children -- Exploring the Relationship of Parental Influences, Motivation for Reading and Reading Achievement in Chinese First Graders -- Reading Disability in Chinese Children. Helping Children with Reading Disability in Chinese: The Response to Intervention Approach with Effective Evidence-Based Curriculum -- Rapid Automatized Naming and Its Unique Contribution to Reading: Evidence from Chinese Dyslexia -- Bilingual and Biliteracy Development in Chinese and English. L1-Induced Facilitation in Biliteracy Development in Chinese and English -- Effect of Early Bilingualism on Metalinguistic Development and Language Processing: Evidence from Chinese-speaking Bilingual Children -- Contributions of Phonology, Orthography, and Morphology in Chinese-English Biliteracy Acquisition: A One-year Longitudinal Study -- Children$1 (Bs literature in Chinese. Chinese Children$1 (Bs Literature in North America -- China and Chinese as Mirrored in Multicultural Youth Literature: A Study of Award-Winning Picture Books Featuring Ethnic Chinese from 1993 to 2009.s
Keywords: Education; Applied linguistics; Psycholinguistics; Language and languages; Literacy; Education; Literacy; Applied Linguistics; Language Education; Psycholinguistics